Molecular characterization of thioester-containing proteins in Biomphalaria glabrata and their differential gene expression upon Schistosoma mansoni exposure - Marquez, J.; Dinguirard, N.; Gonzalez, A.; Kane, A.E.; Joffe, N.R.; Yoshino, T.P.; Castillo, M.G. (Frontiers in Immunology, 2022)
Schistosomiasis is a disease caused by trematode parasites of the genus Schistosoma that affects approximately 200 million people worldwide. Schistosomiasis has been a prevalent problem in endemic areas as there is no vaccine available and currently used anti-helminth medications do not prevent reinfection. Thus, alternative approaches to curtail this human disease are warranted. Understanding the immunobiology of the intermediate host of these parasites, which include the freshwater snail Biomphalaria glabrata, may facilitate the development of novel methods to stop or reduce transmission to humans. Molecules from the thioester-containing protein (TEP) superfamily have been shown to be involved in immunological functions in many animals including corals and humans. In this study we identified, characterized, and compared TEP transcripts and their expression upon S. mansoni exposure in resistant and susceptible strains of B. glabrata snails. Results showed the expression of 11 unique TEPs in B. glabrata snails. These transcripts present high sequence identity at the nucleotide and putative amino acid levels between susceptible and resistant strains. Further analysis revealed differences in several TEPs’ constitutive expression levels between resistant and susceptible snail strains, with C3-1, C3-3, and CD109 having higher constitutive expression levels in the resistant (BS90) strain, whereas C3-2 and TEP-1 showed higher constitutive expression levels in the susceptible (NMRI) strain. Furthermore, TEP-specific response to S. mansoni miracidia exposure reiterated their differential expression, with resistant snails upregulating the expression of both TEP-4 and TEP-3 at 2 hr and 48 hr post-exposure, respectively. Further understanding the diverse TEP genes and their functions in invertebrate animal vectors will not only expand our knowledge in regard to this ancient family of immune proteins, but also offer the opportunity to identify novel molecular targets that could aid in the efforts to develop control methods to reduce schistosomiasis transmission.